2016
DOI: 10.1016/j.jneuroim.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Blood-CSF barrier and compartmentalization of CNS cellular immune response in HIV infection

Abstract: HIV infection is persistent in the CNS, to evaluate the compartmentalization of the CNS immune response to HIV, we compared soluble markers of cellular immunity in the blood and CSF among HIV- (n=19) and HIV+ (n=68), as well as among HIV participants with or without CSF pleocytosis. Dysfunction of the blood cerebrospinal fluid barrier (BCSFB) was common in HIV participants. CSF levels of TNFα, IFNγ, IL-2, IL-6, IL-7, IL-10, IP-10, MIP-1α, MIP-1β, and RANTES were significantly higher in participants with CSF pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…(8) The cellular immune response to HIV in the CSF was different from that in serum. It was stronger in the CNS than in the peripheral blood, indicating that the CNS cellular immune response in HIV infection was compartmentalized, in accordance with previously described (de Almeida et al, 2016B). (9) Several biomarkers had levels higher in the CSF than serum, clearly showing intrathecal production.…”
Section: Discussionsupporting
confidence: 90%
“…(8) The cellular immune response to HIV in the CSF was different from that in serum. It was stronger in the CNS than in the peripheral blood, indicating that the CNS cellular immune response in HIV infection was compartmentalized, in accordance with previously described (de Almeida et al, 2016B). (9) Several biomarkers had levels higher in the CSF than serum, clearly showing intrathecal production.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, previous studies found similar frequencies of HIVC and B neurological and psychiatric manifestations as well as similar stimulation of ß-chemokines and inflammatory bio-markers in the CSF (de Almeida et al 2013, 2016a, b). These findings are contrary to a previous report that HIV-1 subtype C was less neuropathogenic than subtype B (Satishchandra et al 2000).…”
Section: Discussionsupporting
confidence: 65%
“…(7) The cellular immune response to HIV in the CSF was different from that in the serum. The response was stronger in the CNS than that in the peripheral blood, indicating that the CNS cellular immune response was compartmentalized (de Almeida et al 2016a). (8) The levels of several biomarkers were higher in the CSF than those in the serum, strongly indicating intrathecal production.…”
Section: Discussionmentioning
confidence: 99%
“…Increased protein expression of MRP1 and Pgp at the BBB further limits the brain penetration of antiretrovirals and may contribute to the variability in response to HIV therapies (140). BCSFB integrity, analyzed by the CSF albumin/serum albumin quotient ( Q Alb = Alb CSF /Alb serum ), was reduced in HIV patients but not in uninfected controls; however, there is a lack of information on transporter expression in choroid plexus epithelial cells in HIV infection (143).…”
Section: Changes In Expression/function Of Bbb and Bcsfb Transportersmentioning
confidence: 99%